Teachers’ Perception on Using Digital Storytelling in English Learning - Widiyanti, Amelia Kusuma; ZULIKHATIN NUROH, ERMAWATI (Universitas Muhammadiyah Sidoarjo, 2025)
General background: The rapid growth of digital technology has transformed education, creating opportunities for integrating interactive media into classroom learning. Specific background: One promising approach is Digital Storytelling, which combines narrative with multimedia elements such as text, images, audio, and video, particularly useful in language learning. Knowledge gap: While many studies have examined the benefits of Digital Storytelling for students, limited attention has been given to teachers’ perspectives in secondary school contexts. Aims: This study explores teachers’ perceptions of implementing Digital Storytelling in junior high school English classes. Results: Findings from qualitative descriptive research with a grade nine teacher reveal that Digital Storytelling increases teachers’ confidence in using technology, supports students’ writing skill development, and encourages creative and imaginative thinking. Novelty: The study highlights how teachers not only perceive Digital Storytelling as a pedagogical tool but also as a catalyst for fostering 21st-century competencies in the classroom. Implications: These insights suggest that integrating Digital Storytelling in English instruction can strengthen teachers’ pedagogical practices and provide students with more engaging, creative, and technologically adaptive learning experiences. Highlights: Reveals teachers’ perspective on Digital Storytelling in English classrooms. Shows its role in building students’ writing and creativity. Provides insights into integrating technology with pedagogy. Keywords: Digital Storytelling, Teachers’ Perception, Junior High School, English, Writing Skills